TAPA-1, the target of an antiproliferative antibody, defines a new family of transmembrane proteins. - Oren, R (1990)
A murine monoclonal antibody was identified by its ability to induce a reversible antiproliferative effect on a human lymphoma cell line. Immunoprecipitation studies revealed that the antibody reacted with a 26-kilodalton cell surface protein (TAPA-1). A diverse group of human cell lines, including hematolymphoid, neuroectodermal, and mesenchymal cells, expressed the TAPA-1 protein. Many of the lymphoid cell lines, in particular those derived from large cell lymphomas, were susceptible to the antiproliferative effects of the antibody. TAPA-1 may therefore play an important role in the regulation of lymphoma cell growth. A cDNA clone coding for TAPA-1 was isolated by using the monoclonal antibody to screen an expression library in COS cells. Analysis of the deduced amino acid sequence indicated that the protein is highly hydrophobic and that it contains four putative transmembrane domains and a potential N-myristoylation site. TAPA-1 showed strong homology with the CD37 leukocyte antigen and with the ME491 melanoma-associated antigen, both of which have been implicated in the regulation of cell growth.